Sea-Salt Aerosol Mass Concentration Oscillations after Rainfall, Derived from Long-Term Measurements in Lampedusa (Central Mediterranean). (26th April 2012) - Kishcha, P.; Starobinets, B.; Udisti, R.; Becagli, S.; di Sarra, A.; Sferlazzo, D.; Bommarito, C.; Alpert, P.
Abstract : Sea-salt aerosol (SSA) is the dominant contributor to cloud condensation nuclei over ocean areas, where wind speed is significant. Thereby, SSA could affect cloud formation and play an important role in the Earth weather and climate. Rainfall could produce large impact on SSA concentration due to wet removal processes. An analysis of changes in sea-salt aerosol concentration after rainfall is essential for a deeper understanding of the process of SSA loading in the boundary layer. The current experimental study focused on analyzing time variations of SSA mass concentration after rainfall, on the basis of long-term daily SSA measurements during the three-year period 2006–2008, at the tiny Mediterranean island of Lampedusa (Central Mediterranean). To study the effect of rainfall on SSA time variations, we used the superposed epoch method. We applied this approach to differing rainfall events related to different months and atmospheric/sea conditions. Integrated processing was applied to SSA concentration anomalies, in order to filter out random variability. Observational evidence of SSA mass concentration oscillations after rainfall with a maximum on the 2nd day and a minimum on the 4th day was obtained. The knowledge of SSA variations after rainfall is important for validating rainout parameterization in existing sea-salt aerosol and climate models.